A Survey Study of Participation of Scheduled Caste in Business Activities - Kumar, Axey; Mittal, Shwetabh (Journal of Commerce and Trade, 2012)
The author of present research paper is a research scholar of C C S University, Meerut and who has submitted his research study in the university last year. His research work belongs to the study of economic status of scheduled caste in district Meerut and district Saharanpur. In his research work he examined the economic progress made by the people of scheduled caste community of the Area of the study with regard to their education, employment, opportunities in business sector etc.The author of the present paper, who belongs to a scheduled caste family, made an effort to analyse the reasons of non-acceptance of scheduled caste people by the business community of India. For the purpose he interviewed 1000 families of scheduled castes of district Meerut and district Saharanpur and found that 2369 people of these families were engaged in different economic activities. The results of the study are presented in the present research paper in a interactive manner.